Recalibrating Europe's semi-sovereign welfare states - Anton Hemerijck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
Since the late 1970s, all the developed welfare states of the European Union (EU) have been recasting the basic policy mix on which their national systems of social protection were built after 1945. Intensified global competition, industrial restructuring, budgetary austerity, changing family relations and demographic ageing have thrown into question the once sovereign and stable welfare systems of the Golden Age'. Moreover, domestic issues of work and welfare have more recently become ever more intertwined with processes of European political and economic integration. In this respect, it is fair to say that in the EU we have entered an era of semi-sovereign welfare states. Together, these forces have produced a momentum of system change that goes far beyond the popular notion of welfare state 'retrenchment'. The 'new' welfare edifice suggests a departure from a 'politics against markets' social-protection perspective, towards more of a 'politics with markets', social-investment approach. This paper tries to capture the comprehensive character of the ongoing effort to recast the architecture of the post-war social contract in terms of the concept of welfare recalibration for both heuristic and prescriptive purposes. It also addresses the engagement of the EU in ongoing processes of recalibrating Europe's semi-sovereign welfare states. In the policy debate the term 'European social model' is often invoked. Yet such generalisations gloss over the immense differences in welfare state development, design and institutional make-up across the EU's 25 member states and, as a consequence, fail to capture the complexity of 'contingently convergent' reform trajectories in the recent period. – – Seit den späten 70er Jahren stellen alle hochentwickelten Sozialstaaten der EU den Mix an Sozial-Politiken, wie er nach 1945 in den jeweiligen Staaten geschaffen wurde, auf den Prüfstand. Die intensivierte Globalisierung, der Umbau der industriellen Produktion, Budgetprobleme, sich verändernde Familienbeziehungen und eine alternde Bevölkerung führen zu immer mehr Zweifeln an dem lange Zeit bewährten und stabilen wohlfahrtsstaatlichen System des goldenen Zeitalters. Dazu kommt, dass in letzter Zeit bisher nationale Themen wie Arbeit und Wohlfahrtsstaat immer stärker in die Prozesse der europäischen Integration hineingezogen werden. In diesem Blickwinkel gesehen ist es angemessen zu sagen, dass in der EU die Ära der nur noch halbsouveränen Staaten begonnen hat. All dies zusammengenommen kann man sagen, dass sich eine Konstellation ergeben hat, in der sich ein Systemwechsel vollzieht, der weit über die populäre Wahrnehmung der Öffentlichkeit vom 'Abbau des Sozialstaats' hinausgeht. Die Konstruktion der neuen Wohlfahrtspolitik bedeutet den Abschied von einer Politik des sozialen Beschützens 'gegen die Märkte' hin zu einer Politik sozialer Investitionen 'mit den Märkten'. In diesem Papier wird versucht, die umfassende Bedeutung der fortdauernden Bemühungen zur Umgestaltung der Architektur des Sozialkontrakts aus der Nachkriegszeit zu erfassen - und zwar sowohl für heuristische Zwecke wie auch als Handlungsanleitung. Die Analyse bezieht sich auch auf das Engagement der EU in den andauernden Prozessen, die halbsouveränen Wohlfahrtsstaaten Europas neu zu 'justieren'. In politischen Diskussionen wird oft der Begriff vom 'Europäischen Sozialmodell' beschworen.
Keywords: 330; Sozialstaat; Sozialreform; EU-Sozialpolitik; EU-Staaten